Pembuatan Aplikasi Kearsipan Archelo di Kelurahan Wonocolo Kabupaten Sidoarjo - Latifatun Nur Azizah; Varrel Raihansyah Judhityo Arifin; Yansi Dwi Safitri; Yadhira Oza Mawarda; Yuni Lestari (Perspektif Administrasi Publik dan hukum, 2026)
Records management is an essential aspect of supporting effective, efficient, and accountable public administration. Wonocolo Village Office still encounters various challenges in records management, including limited storage space, difficulties in retrieving documents, the risk of data loss, and the suboptimal utilization of information technology in archival processes. This study aims to develop ARCHELO (Archive Kelurahan Wonocolo), a digital archival application designed to improve records management efficiency and support better public services. The study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, and surveys involving village officials to identify user needs and existing archival management problems. The findings indicate that ARCHELO facilitates digital records management through features such as incoming and outgoing correspondence management, document retrieval, user access control, and integrated document templates. The implementation of the application provides greater convenience in storing, retrieving, and securing records, thereby reducing the risk of document loss and enhancing the effectiveness of administrative work within the village office. The development of ARCHELO is expected to serve as a solution for modernizing archival systems within village and local government institutions and to support the establishment of more organized, efficient, and sustainable administrative governance.